Asuhan Keperawatan Gerontik Pada Pasien Dengan Stroke Di Panti Sosial Tresna Werdha Sabai Nan Aluih Sicincin Kabupaten Padang Pariaman - Elsa Dita Syafitri; Sandra Dewi; Mike Asmaria; Armaita . (CV. ITTC INDONESIA, 2026)
Stroke is the leading cause of disability in the world and ranks second as a cause of death after heart disease. Data shows that every year there are around 13.7 million new cases of stroke with a death rate reaching approximately 5.5 million people. Data obtained at the PSTW Sabai Nan Aluih Sicincin, Padang Pariaman Regency, shows that stroke ranks fourth with a total of 12 cases. The purpose of this researcher is to provide nursing care to patients with stroke at the Sabai Nan Aluih Sicincin Social Home for the Elderly, Padang Pariaman Regency. The research method used is a case study on one client with a nursing process approach that includes assessment, nursing diagnosis, intervention, implementation, and evaluation. The assessment was conducted on February 11–16, 2026. The results of the assessment showed that the client experienced impaired physical mobility, self-care deficits, and a risk of falling due to muscle weakness and balance disorders. Interventions provided included Range of Motion (ROM) exercises, assistance with daily activities, health education, and fall risk prevention. The evaluation results obtained after 5 days of implementation showed an increase in nursing problems, with muscle strength in the right lower extremity being 3%, an increase in self-care skills, and a decrease in the risk of falls. The conclusion of this study is that comprehensive geriatric nursing care can help improve the functional abilities of elderly people with stroke. It is recommended that clients and caregivers regularly exercise, maintain a healthy lifestyle, and undergo regular health checks to prevent complications and stroke recurrence.